Gene Coexpression Network Characterizing Microenvironmental Heterogeneity and Intercellular Communication in Pancreatic Ductal Adenocarcinoma: Implications of Prognostic Significance and Therapeutic Target - Wu, Chengsi; Liu, Yizhen; Wei, Dianhui; Tao, Li; Yuan, Lili; Jing, Tiantian; Wang, Boshi (Frontiers in Oncology, 2022)
Background: Pancreatic ductal adenocarcinoma (PDAC) is characterized by intensive stromal involvement and heterogeneity. Pancreatic cancer cells interact with the surrounding tumor microenvironment (TME), leading to tumor development, unfavorable prognosis and therapy resistance. Herein, we aim to clarify a gene network indicative of TME features and find a vulnerability for combating pancreatic cancer. Methods: Single-cell RNA sequencing data processed by the Seurat package were used to retrieve cell component marker genes (CCMGs). Correlation networks/modules of CCMGs were determined by WGCNA. Neural network and risk score models were constructed for prognosis prediction. Cell–cell communication analysis was achieved by NATMI software. The effect of the ITGA2 inhibitor was evaluated in vivo by using a KrasG12D-driven murine pancreatic cancer model. Results: WGCNA categorized CCMGs into eight gene coexpression networks. TME genes derived from the significant networks were able to stratify PDAC samples into two main TME subclasses with diverse prognoses. Furthermore, we generated a neural network model and a risk score model that robustly predicted prognosis and therapeutic outcomes. Functional enrichment analysis of hub genes governing gene networks revealed a crucial role of cell junction molecule-mediated intercellular communication in PDAC malignancy. Pharmacological inhibition of ITGA2 counteracts the cancer-promoting microenvironment and ameliorates pancreatic lesions in vivo. Conclusion: By utilizing single-cell data and WGCNA to deconvolute the bulk transcriptome, we exploited novel PDAC prognosis-predicting strategies. Targeting the hub gene ITGA2 attenuated tumor development in a PDAC mouse model. These findings may provide novel insights into PDAC therapy.